Developmental Education and Early Childhood Cognitive Growth: Evidence from Kindergartens in Jakarta - Arisandi; Syamsul Akbar (Generasi Sains Indonesia, 2025)
Early childhood is a crucial phase for establishing the foundations of lifelong learning, yet the effectiveness of developmental approaches in Indonesia’s kindergartens remains limited in research. This study investigates how developmental education supports children’s cognitive growth in Jakarta, focusing on literacy, numeracy, working memory, and language development. Using a mixed-methods design, standardized cognitive assessments were combined with observations and interviews with teachers and parents. The sample involved 200 kindergarten children from ten schools representing diverse socioeconomic backgrounds. Results show notable cognitive gains over one academic year, particularly in literacy and language abilities, while improvements in working memory were smaller but still meaningful. However, socioeconomic disparities were visible, with children in higher-SES schools benefiting from richer learning environments. Observational data revealed that although play-based and child-centered activities were widely applied, rote instruction remained common in numeracy lessons. Teachers and parents generally supported developmental approaches, yet many parents emphasized early English learning, reflecting societal pressures. Overall, findings indicate that developmental education can enhance school readiness, but its benefits are unevenly distributed. Strengthening teacher capacity, improving resources in low-SES schools, and aligning expectations with parents are necessary to ensure more inclusive and equitable early childhood education in Indonesia.